2023
DOI: 10.1101/2023.02.11.528119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Somatotopic organization among parallel sensory pathways that promote a grooming sequence inDrosophila

Abstract: Mechanosensory neurons located across the body surface respond to tactile stimuli and elicit diverse behavioral responses, from relatively simple stimulus location-aimed movements to complex movement sequences. How mechanosensory neurons and their postsynaptic circuits influence such diverse behaviors remains unclear. We previously discovered that Drosophila perform a body location-prioritized grooming sequence when mechanosensory neurons at different locations on the head and body are simultaneously stimulate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 115 publications
(170 reference statements)
0
5
0
Order By: Relevance
“…Almost 95% of these neurons were in the neck connective, antennal nerve, and maxillary-labial nerve. Although afferents are truncated in our reconstruction, Schlegel et al (Philipp Schlegel et al 2023) along with other community members (Eichler et al 2023;H. Kim et al 2020) were able to determine the sensory organs corresponding to 5,362 of the 5,495 non-visual sensory neurons (Fig.…”
Section: Afferent and Efferent Neuronsmentioning
confidence: 74%
See 2 more Smart Citations
“…Almost 95% of these neurons were in the neck connective, antennal nerve, and maxillary-labial nerve. Although afferents are truncated in our reconstruction, Schlegel et al (Philipp Schlegel et al 2023) along with other community members (Eichler et al 2023;H. Kim et al 2020) were able to determine the sensory organs corresponding to 5,362 of the 5,495 non-visual sensory neurons (Fig.…”
Section: Afferent and Efferent Neuronsmentioning
confidence: 74%
“…Neurons in Drosophila are considered to be identifiable across hemispheres and individuals (Luan et al 2006;Pfeiffer et al 2010), enabling cell type classification of all neurons in FlyWire -such classification is useful for generating testable hypotheses about circuit function from the connectome. FlyWire community members, experts in diverse regions of the fly brain, have shared 91,649 annotations of 59,548 neurons (Supplemental Information 4), including the majority of sexually-dimorphic neurons (Deutsch et al, in prep), sensory neurons (Eichler et al 2023), as well as a diversity of cell types in the optic lobes and SEZ (Fig. 2f), two brain regions not covered in the hemibrain connectome.…”
Section: Cell Types and Other Annotationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank Clare Pilgrim, Alex McLachlan and David Osumi-Sutherland for incorporating our predictions into Virtual Fly Brain. Researchers 18 , 50 , 65 , 74 , 76 , 90 , 114 , 202 , 208 , 209 , 210 , 211 have already utilized our preprinted results to formulate neurobiological hypotheses. The most reliable predictions align across hemispheres, exhibit cohesion within a cell type, adhere to Lacin’s law and remain consistent across datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Frontiers in Physiology frontiersin.org mechanosensory neurons that control grooming of head regions establish a somatotopic brain map (Eichler et al, 2023). Neurogenetic, imaging and behavioral studies identified mushroom body neurons that decode the value rather than the specificity of an odor (Das Chakraborty et al, 2022;Villar et al, 2022), whereas Mohamed et al uncovered neurons implicated in intensity-dependent odor discrimination learning.…”
Section: Figurementioning
confidence: 99%